The blind need not apply : a history of overcoming prejudice in the orientation and mobility profession - Ferguson, Ronald J., 1956- (Critical concerns in blindness., 2007)
From the Publisher: This book has been a work in progress. In the spring of 2000 I started this project and began to collect data and conduct interviews. I copied every article I could find in the Journal of Visual Impairment and Blindness and its predecessors Outlook for the Blind and New Outlook for the Blind. I was fortunate to locate Blindness the annual publication of the American Association of Workers for the Blind. One of the greatest finds was the library at the American Foundation for the Blind. The library contains dozens of volumes related to orientation and mobility. Within two years I had amassed a considerable collection of resources. I began working through the materials and along the way prepared some papers for various conferences. A dramatic increase in administrative responsibilities, as well as the tyranny of meeting grant deadlines, diverted me from giving concentrated effort to this book. All that changed as I reduced my workload in order to devote almost all my efforts over the past nine months to this project.